'Weak winners' of Women's empowerment: The gendered effects of dairy livestock assets on time poverty in Uganda. (July 2018) - Bain, Carmen; Ransom, Elizabeth; Halimatusa'diyah, Iim
Highlights: Dairy cows provide important economic benefits to households but increase women's time poverty. Women's age, economic status, clean water access, and empowerment levels influence time poverty. Accessing water for cows is challenging due to women's substantial household labor obligations. Women expressed greater dissatisfaction with their amount of leisure time than men.